AFTER THE 2001 ECONOMIC CRISIS IN TURKEY INFLATION-GROWTH INTERACTION (Third Sector Social Economic Review, 2020)
One of the main objectives of economics is the phenomenon of economic growth. Inflation, on the other hand, is a factor that has a determining effect on the basic macroeconomic variables of the economy. In this study were examined the relationship between inflation and growth in Turkey for the period 2003:1-2019:4. Empirical findings showed the suppressive effect of inflation on growth in the period analyzed. It has been demonstrated that the 1% inflation increase reduced growth by about 0.54%. In the study, Engel Granger Cointegration Analysis based on error correction model (ECT) was performed for long term relationship between variables. As a result of the analysis, the existence of a long-term relationship has been proved.
Keywords: Inflation; Growth; Cointegration Analysis; Error Correction Model